Coupling Nanostructured CsNiCr Prussian Blue Analogue to Resonant Microwave Fields. Issue 1 (19th November 2019) - Ghirri, Alberto; Herrero, Christian; Mazérat, Sandra; Mallah, Talal; Moze, Oscar; Affronte, Marco
Abstract: Collective spin excitations in magnetically ordered materials are exploited for advanced applications in magnonics and spintronics. In these contexts, conditions for minimizing dissipative effects are sought in order to obtain long living excitations that can be coherently manipulated. Organic and coordination materials may offer alternative options for their flexibility and low spin–orbit effects. Likewise, ferromagnetic nanostructures provide a versatile platform for hybrid architectures, yet downsizing affects the spin dynamics and needs to be controlled. Here, a systematic investigation on insulating CsNiCr(CN)6 Prussian blue analogue, including isolated nanoparticles dispersed in polyvinylpyrrolidone, mutually interacting nanoparticles embedded in cetyltrimethylammonium, and bulk samples, is reported. Ferromagnetic resonance spectroscopy is performed in a wide temperature range across the bulk ferromagnetic transition occurring at 90 K. This allows us to monitor key parameters through different types of nanostructured samples. It is found that the Gilbert damping parameter of 10 nm nanoparticles compares well (10 −3 ) with values reported for prototypical yttrium iron garnet Y3 Fe5 O12 . Strong coupling with the microwave field of a microstrip resonator is then observed for bulk CsNiCr(CN)6 as well as for interacting nanoparticles. These results clarify conditions for the coherent manipulation of collective spin degrees of freedom in nanostructured coordination materials. Abstract : Ferromagnetic resonance studies on bulk and nanostructured CsNiCr Prussian blue analogue are carried out in a wide temperature range accross the Curie temperature at 90 K. A Gilbert damping parameter of 10 −3 is extracted for isolated nanoparticles, whilst strong coupling between ferromagnetic resonance mode and microwave field is achieved for bulk and interacting nanoparticle samples.